Efficacy of allopurinol and benzbromarone for the control of hyperuricaemia. A pathogenic approach to the treatment of primary chronic gout. Issue 9 (1st September 1998) - Perez-Ruiz, F; Alonso-Ruiz, A; Calabozo, M; Herrero-Beites, A; García-Erauskin, G; Ruiz-Lucea, E
Abstract : OBJECTIVES: To study the efficacy of allopurinol and benzbromarone to reduce serum urate concentrations in patients with primary chronic gout. METHODS: Prospective, parallel, open study of 86 consecutive male patients with primary chronic gout. Forty nine patients (26 normal excretors and 23 under excretors) were given allopurinol 300 mg/day and 37 under excretors benzbromarone 100 mg/day. After achieving steady plasma urate concentrations with such doses, treatment was then adjusted to obtain optimal plasmatic urate concentrations (under 6 mg/dl). RESULTS: Patients receiving allopurinol 300 mg/day showed a mean reduction of plasmatic urate of 2.75 mg/dl (from 8.60 to 5.85 mg/dl) and 3.34 mg/dl (from 9.10 to 5.76 mg/dl) in normal excretors and under excretors respectively. Patients receiving benzbromarone 100 mg/day achieved a reduction of plasmatic urate of 5.04 mg/dl (from 8.58 to 3.54 mg/dl). Fifty three per cent of patients receiving allopurinol and 100% receiving benzbromarone achieved optimal plasma urate concentrations at such doses. The patients with poor results with allopurinol 300 mg/day achieved a proper plasma urate concentration with allopurinol 450 to 600 mg/day, the mean final dose being 372 mg/day. Renal fuction improved and no case of renal lithiasis was observed among benzbromarone treated patients, whose mean final dose was 76 mg/day. CONCLUSION: Benzbromarone is very effective to control plasma urate concentrations at doses ranging from 50 to 100 mg/day. Uricosuric treatment is a suitable approach to the treatment of patients with gout who show underexcretion of urate.